AN ISLAMIC CRIMINAL LAW PERSPECTIVE ON ARTICLE 408 OF LAW NO. 1 OF 2023: Regarding The Display Of Contraceptives - Nasution, Iwan; Khairunnisa Lubis, Laila (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
This research aims to analyze the formulation of criminal law policy in Article 408 of the Indonesian Criminal Code (KUHP) based on juridical, philosophical, and sociological aspects, as well as to examine the regulation of the acts stipulated in Article 408 from the perspective of Islamic criminal law through the method of sadd al dhariah. The research employs a normative juridical method with statutory and conceptual approaches. The legal materials used consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively. The results show that the formulation of criminal law policy in Article 408 of the KUHP is based on juridical aspects in the form of legal certainty and clarity of legal norms, philosophical aspects in the form of child protection and the preservation of moral values, and sociological aspects in the form of society’s need to protect children from information that is inappropriate to their stage of development. From the perspective of Islamic criminal law, the regulation of the acts stipulated in Article 408 of the KUHP is regarded as a preventive measure against harm through the method of sadd al dhariah, namely by blocking the means that may lead to moral corruption. Therefore, the regulation contained in Article 408 of the KUHP functions not only as an effort to prevent harm but also accommodates the implementation of reproductive health education through parties who are legally authorized to provide it.